2014
DOI: 10.1016/j.jegh.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to medications and associated factors: A cross-sectional study among Palestinian hypertensive patients

Abstract: Poor adherence to medications was very common. The findings of this study may be used to identify the subset of population at risk of poor adherence who should be targeted for interventions to achieve better blood pressure control and hence prevent complications. This study should encourage the health policy makers in Palestine to implement strategies to reduce non-compliance, and thus contribute toward reducing national health care expenditures. Better patient education and communication with healthcare profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
93
6
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(132 citation statements)
references
References 20 publications
22
93
6
11
Order By: Relevance
“…A study in north-west Ethiopia [37] also found that patients with no and one co-morbidity were more likely to adhere to their treatment than those with two (AOR = 2.50, 95% CI: 1.01 -6.21) or more than two co-morbidities (AOR = 2.68, 95% CI: 1.07 -6.71). However, having no other chronic disease ( = 0.009) was a significant factor influencing MNA among hypertensive patients in Palestine [38].…”
Section: Demographic Factorsmentioning
confidence: 87%
See 3 more Smart Citations
“…A study in north-west Ethiopia [37] also found that patients with no and one co-morbidity were more likely to adhere to their treatment than those with two (AOR = 2.50, 95% CI: 1.01 -6.21) or more than two co-morbidities (AOR = 2.68, 95% CI: 1.07 -6.71). However, having no other chronic disease ( = 0.009) was a significant factor influencing MNA among hypertensive patients in Palestine [38].…”
Section: Demographic Factorsmentioning
confidence: 87%
“…A study in Palestine found that patients with hypertension were not adhering to their medication due to the fear of dependent on medicines (AOR = 8.00; 95% CI: (2. 44 -26.19) [38]. Similarly avoiding side effects of drugs (AOR = 3.0; 95% CI: 1.4 -6.7) was an important reason for non-adherence to their treatment regimen among hypertensive patients in Nigeria [42].…”
Section: Perceptions Regarding Hypertension and Its Severitymentioning
confidence: 92%
See 2 more Smart Citations
“…While oral agents pose many notable advantages when compared to conventional parenteral drugs, including enhanced convenience of self‐administration, reduced hospital and societal costs, and improved patient engagement in their own care 1, 2, 3, 4, these benefits must be balanced against growing concerns regarding poor compliance to treatment and its potentially negative impact on outcomes 1, 2, 3, 4, 5, 6. Suboptimal adherence to medications is a commonly recognized problem for many chronic medical conditions, such as hypertension and diabetes mellitus, where it has been shown to compromise drug effectiveness 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%